Arthroscopic three-corner or lunocapitate arthrodesis: technical tips and early outcomes. Issue 3 (1st June 2022) - Politikou, Olga; Reissner, Lisa; Besmens, Inga S.; Calcagni, Maurizio
Abstract: The purpose of the study is to present a technical approach for arthroscopic three-corner or lunocapitate arthrodesis with mini-open scaphoid excision and to report about the early clinical and functional results. The median surgery time was 112 min with shorter times achieved once mastering the technique. Radiological and clinical union was observed in 11 out of 12 patients in a median time of five months. For final assessments nine patients were included with a median follow-up of 15 months. Wrist extension and flexion after surgery decreased to 58 and 62% of preoperative measurements and represented 37 and 42% of the unaffected side. Grip strength also decreased to 80% of the preoperative value and 57% of the unaffected side. All patients reported significant pain relief and functional improvement. Arthroscopic three-corner or lunocapitate arthrodesis was a safe, reliable and minimally invasive technique for treating wrist osteoarthritis, while it was technically demanding and time-consuming during learning curve.